Uncertain future and uncertain projections: assessing extinction risks in European salamanders from projected chytrid fungus invasion using IUCN Criterion E - Stefano Canessa; Antonio Romano; Dino Biancolini; Mattia Iannella; Ilaria Bernabò; Daniele Salvi; Leonardo Vignoli; Enrico Lunghi; Andrea Costa; Edoardo Razzetti; Gentile Francesco Ficetola (Acta Herpetologica)
Amphibians are among the most threatened vertebrates globally, and their conservation status continues to decline. In the updated Global Amphibian Assessment (GAA2), the use of IUCN Criterion E, which projects extinction risks through quantitative models, highlighted southern Europe as a hotspot for salamander extinction risk due to the risk of invasion by the fungal pathogen Batrachochytrium salamandrivorans (Bsal). In particular, for five Italian salamander species, risk categories were elevated significantly based on Criterion E, from Vulnerable or lower to Endangered or Critically Endangered. This increased reliance on Criterion E raises concerns regarding its treatment of uncertainty, as these projections depend heavily on assumptions about Bsal spread, environmental suitability, and host dynamics. Limited exploration of alternative scenarios and reliance on extreme parameter values ​​may result in inflated extinction risk estimates. We emphasize the need for improved documentation of uncertainty and integration of diverse expert opinions in extinction risk assessments, to balance proactive conservation planning with robust scientific methodology.